Advanced RuO2-based electrocatalysts for oxygen evolution reaction: A perspective from coordination structures - Qian Sun; Jiaxin Zhang; Wei Kong Pang; Bernt Johannessen; Peng Li; Guoqiang Zhao; Huaming Yang (Materials Today Catalysis)
Proton exchange membrane water electrolysis (PEMWE) is a promising technology for green hydrogen production, but its efficiency is limited by the sluggish oxygen evolution reaction (OER). RuO2-based electrocatalysts exhibit superior intrinsic OER activity compared to IrO2, yet their practical application is hindered by poor stability due to lattice oxygen overoxidation and Ru overoxidation. Recent advances highlight that modulating the local coordination environment of RuO2 through doping, strain engineering, and defect control can not only optimize the OER pathways but also regulate the intrinsic activity of active sites, thereby achieving more balanced OER activity and stability. Meanwhile, computational investigations have also revealed deep insights into the catalytic performance of RuO2 from the perspective of local coordination structures. Therefore, in this review, we start by discussing the OER mechanisms and common structural descriptors of the activity and stability of RuO2. Then, we explore the relationship between structural regulation strategies and the OER performance of RuO2 and analyze how coordination engineering influences catalytic behavior, establishing a designing framework for high-performance catalysts. Finally, we outline key challenges and future directions for RuO2-based OER electrocatalysts in PEMWE applications.